Photovoltaic surfaces enable clonal myoblastic cell release using visible light as external stimulation. Issue 3 (27th January 2016) - Bhuyan, Mohammod Kabir; Rodriguez, Jorge; Tseng, Tzu‐Liang Bill; Boland, Thomas
Abstract: Many new biomedical approaches to treating disease require the supply of cells delivered to an injured or diseased organ either individually, collectively as aggregates or sheets, or encapsulated with a scaffold. The collection of cells is accomplished by using enzymatic digestion witch suffer from the need to remove the enzymes after digestion. In addition, enzymatic methods are not applicable for all cells, cell aggregates, cell sheets or 3D structures. The objective of this study was to investigate the release of cultured cells from silicon based Photovoltaic (PV) surfaces using a light source as external stimulation. C2C12 myoblasts were cultured on the negative surface of a PV device and upon confluence they were exposed to light. The amount of released cells was quantified as a function light exposure. It was found that light exposure at 25 000 lux for one hour caused equivalent cell release from the PV surface than trypsination. The released cells are viable and can be re‐cultured if needed. This mechanism may offer an alternative method to release excitable cells without using an enzymatic agent. This may be important for cell therapy if larger cell structures such as sheets need to be collected. Abstract : The authors hypothesize that cells cultured on the surfaces of photovoltaic elements may be released by applying visible radiation to the element. The light will induce a surface charge on the element causing cells to be released by static repulsion. Herein, the authors study the amount and the viability of myoblasts cells released from a photovoltaic element upon light exposure. The results show that the photovoltaic elements are suitable substrates for cell culture, and the cells released from the elements upon light stimulation are viable and can be used for further experiments.